183W NMR Spectroscopy Guides the Search for Tungsten Alkylidyne Catalysts for Alkyne Metathesis. (24th September 2020) - Hillenbrand, Julius; Leutzsch, Markus; Gordon, Christopher P.; Copéret, Christophe; Fürstner, Alois
Abstract: Triarylsilanolates are privileged ancillary ligands for molybdenum alkylidyne catalysts for alkyne metathesis but lead to disappointing results and poor stability in the tungsten series. 1 H, 183 W heteronuclear multiple bond correlation spectroscopy, exploiting a favorable 5 J ‐coupling between the 183 W center and the peripheral protons on the alkylidyne cap, revealed that these ligands upregulate the Lewis acidity to an extent that the tungstenacyclobutadiene formed in the initial [2+2] cycloaddition step is over‐stabilized and the catalytic turnover brought to a halt. Guided by the 183 W NMR shifts as a proxy for the Lewis acidity of the central atom and by an accompanying chemical shift tensor analysis of the alkylidyne unit, the ligand design was revisited and a more strongly π‐donating all‐alkoxide ligand prepared. The new expanded chelate complex has a tempered Lewis acidity and outperforms the classical Schrock catalyst, carrying monodentate tert ‐butoxy ligands, in terms of rate and functional‐group compatibility. Abstract : Silanolate ligands excel with molybdenum alkylidynes but are found to be inadequate for tungsten in that they impart undue Lewis acidity. This effect is manifested in the 183 W NMR shifts, which are surprisingly easy to record by 1 H, 183 W HMBC experiments. As a consequence, the ligand scaffold was redesigned and an unprecedented chelate alkoxide complex, which is a new lead in the quest for competent tungsten‐based alkyne metathesis catalysts, was developed.